Graphic medicine meets human anatomy: The potential role of comics in raising whole body donation awareness in Italy and beyond. A pilot study. Issue 2 (7th December 2022) - De Stefano, Alessia; Rusciano, Isabella; Moretti, Veronica; Scavarda, Alice; Green, Michael J.; Wall, Shelley; Ratti, Stefano
Abstract: Cadaver dissection has always played a fundamental role in medical education. However, especially in Italy, the topic of body donation has remained partially unknown for years. The current study analyses graphic medicine as a new possible communication tool, evaluating and reflecting, with second‐year students enrolled in the International School of Medicine and Surgery at the University of Bologna, about its potentialities for body donation awareness‐raising in both the scientific community and the general population. For the first time in an Italian University, two graphic medicine workshops were organized focusing on human anatomy and body donation. Seminars were positively evaluated by students using a four items Likert‐scale question: mean 3.54 (± SD 0.73) for the Likert question about the experiences of the workshops; 3.88 (± 0.33) for the Likert question regarding the use of graphic medicine in body donation awareness campaigns among the general population; 3.59 (± 0.65) for the Likert question regarding the use of graphic medicine in body donation awareness campaigns among the scientific community. Furthermore, the open‐ended questions included in the anonymous questionnaire were analyzed using the constructivist grounded qualitative analysis, whence various themes emerged. Finally, five graphic medicine projects about body donation were created by students, proving their interest in testing this method to promote body donation, focusing the attention on different communicative aspects. Considering the results of this pilot study, the co‐creative collaborative use of graphic medicine could be evaluated as an additional strategy to increase body donation awareness‐raising in Italy and beyond, especially in the non‐experts' community.